Repeated Mild Closed Head Injuries Induce Long-Term White Matter Pathology and Neuronal Loss That Are Correlated With Behavioral Deficits. (June 2018) - Gold, Eric M.; Vasilevko, Vitaly; Hasselmann, Jonathan; Tiefenthaler, Casey; Hoa, Danny; Ranawaka, Kasuni; Cribbs, David H.; Cummings, Brian J.
An estimated 5.3 million Americans are living with a disability from a traumatic brain injury (TBI). There is emerging evidence of the detrimental effects from repeated mild TBIs (rmTBIs). rmTBI manifests its own unique set of behavioral and neuropathological changes. A subset of individuals exposed to rmTBI develop permanent behavioral and pathological consequences, defined postmortem as chronic traumatic encephalopathy. We have combined components of two classic rodent models of TBI, the controlled cortical impact model and the weight drop model, to develop a repeated mild closed head injury (rmCHI) that produces long-term deficits in several behaviors that correlate with neuropathological changes. Mice receiving rmCHI performed differently from 1-hit or sham controls on the elevated plus maze; these deficits persist up to 6 months postinjury (MPI). rmCHI mice performed worse than 1-hit and control sham mice at 2 MPI and 6 MPI on the Morris water maze. Mice receiving rmCHI exhibited significant atrophy of the corpus callosum at both 2 MPI and 6 MPI, as assessed by stereological volume analysis. Stereological analysis also revealed significant loss of cortical neurons in comparison with 1-hit and controls. Moreover, both of these pathological changes correlated with behavioral impairments. In human tau transgenic mice, rmCHI induced increases in hyperphosphorylated paired helical filament 1 tau in the hippocampus. This suggests that strategies to restore myelination or reduce neuronal loss may ameliorate the behavioral deficits observed following rmCHI and that rmCHI may model chronic traumatic encephalopathy in human tau mice.